The impact of psychological factors on bereavement among frontline nurses fighting Covid-19 - Islam Azizpour; Saeid Mehri; Hamed Rezakhani Moghaddam; Alireza Mirzaei; Aghil Habibi Soola (Elsevier, 2021)
The COVID-19 pandemic has considerably changed the workplace and social relationships of nurses. As potential factors, uncertainty, stigma, and exposure of nurses' families to risk have disturbed the process of providing healthcare services for patients infected by COVID-19. Accordingly, this study aimed at determining the impact of psychological factors on stigma among frontline nurses fighting COVID-19. The extant paper was carried out based on the descriptive-analytical method for April-June 2020. A total of 312 nurses working in educational-medical centers in Ardabil, Iran, were selected using the census method to participate in this research. To collect data, demographic features, stigma, mental health, perceived stress, and hardiness questionnaires were used. The collected data were analyzed using statistical correlation tests, multivariate regression, and descriptive tests through SPSS v.22 Software. The mean score of stigma in nurses equaled 28.36 ± 10.55. Results of the correlation coefficient showed a positive relationship between the mean score of stigma and stress (P ≤ 0.01) as well as the negative relationship between mental health and hardiness (P ≤ 0.01). Multivariate regression analysis indicated that mental health could be the predictor of stigma. Therefore, these factors should be identified and controlled to mitigate stigma under such critical circumstances.